Kualitas Dalam Memproduksi Suatu Barang Dan Jasa - Tanjung, Devi Purnama; Zega, Janvany Herni Yanti; Zai, Irene Indrawati; Harefa, Dian Indah Putri (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
Quality in the production of goods and services is an important element that affects customer satisfaction and the competitiveness of the company. In the context of the production of goods, quality is determined by factors such as the selection of raw materials, efficient production processes, and strict quality control. Meanwhile, in the production of services, quality is more related to customer perceptions of the services provided, which are influenced by the expertise of the workforce, the service process, and the overall customer experience. Factors that affect quality include available resources, managerial skills, technology, and company culture. To maintain and improve quality, companies need to implement a quality management system, provide continuous training to employees, and always focus on continuous improvement. With the right strategy, companies can ensure high quality, which ultimately supports customer satisfaction and business sustainability.